Numerical Study of Drilling Process Using Finite Element Method - Abdul Aziz, Muhamad Afiq; Abdullah , Haslina (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Like most machining process, cutting tool deflection in drilling is affected the efficiency of machining process. Nowadays simulation studies have been widely used in predict the cutting tool deflection and at the same time it can reduce the cost of manufacturing. Therefore, in this current research, a simulation procedure has been developed to study the cutting tool deflection in drilling process. Other than that, the objective of this study is to analyse the stress and deflection acting on cutting tool. Finite Element Analysis (FEA) has been used in this study which is Abaqus software has been implemented in order to simulate and analyse the results. A three-dimensional model of cutting tool has been develop and a force loading has been applied at the tip of cutting tool. Based on the simulation, it has been found, the deflection of cutting tool is related to the results of stress distribution and displacement along the path that has been created along cutting tool. In addition, it has been stated that the maximum stress distribute on the cutting tool can be seen from different colour contour and the maximum value is 4.707e+03 which is occurred at the tip of cutting tool. While for the value of displacement, the maximum value is 1.640e-08. Lastly, by using finite element method, many parameters of cutting tool and drilling process can be studied to obtain the best cutting parameters and enhance the performance of machining process